Respuesta :

(-4,6); (0,2); (4,-2)

First step is to solve the given equation for y. So, subtract x from each sides to isolate y. Therefore,

x + y - x = 2 - x

y = 2 -x.

Next step is to plug in the values of x = -4, 0 and 4 to get the corresponding values of y's so that we can get the correct order pair.

Let's plug in x = -4 now.

So, y = 2 - ( - 4) = 2 + 4 = 6

So, the first order pair is (- 4, 6).

For x = 0, y = 2 - 0 = 2

Second order pair is (0, 2).

For x = 4, y = 2 - 4 = -2.

Third order pair is (4, -2)

So, third list of order pairs (-4, 6), (0, 2), (4, -2) represent the solutions.

Hope this helps you!

ACCESS MORE